2023
DOI: 10.1108/jedt-08-2022-0428
|View full text |Cite
|
Sign up to set email alerts
|

Circular building adaptability in adaptive reuse: multiple case studies in the Netherlands

Abstract: Purpose The application of circular building adaptability (CBA) in adaptive reuse becomes an effective action for resource efficiency, long-lasting usability of the built environment and the sped-up transition to a circular economy (CE). This paper aims to explore to which extent CBA-related strategies are applied in adaptive reuse projects, considering enablers and obstacles. Design/methodology/approach A stepwise theory-practice-oriented approach was followed. Multiple-case studies of five circular adaptiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…The interviews revealed that economic incentives and regulatory support were the two most important factors enabling CBA. This observation aligned with previous research identifying barriers to implementing adaptability in housing design (Hamida et al ., 2023; Tarpio et al ., 2021). Hopefully, upcoming economic and regulatory frameworks supporting circularity will encourage the construction of more adaptable buildings.…”
Section: Concluding Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The interviews revealed that economic incentives and regulatory support were the two most important factors enabling CBA. This observation aligned with previous research identifying barriers to implementing adaptability in housing design (Hamida et al ., 2023; Tarpio et al ., 2021). Hopefully, upcoming economic and regulatory frameworks supporting circularity will encourage the construction of more adaptable buildings.…”
Section: Concluding Discussionsupporting
confidence: 91%
“…As concluding recommendations of their study, Hamida et al (2022) highlight the need for a better understanding of how CBA could be enabled by design strategies, and "a practical and evidence-based framework" (Hamida et al, 2022, p. 64) for the implementation of the concept. Additionally, Hamida et al (2023) explored design strategies of CBA in adaptive reuse and concluded (similarly to previous research on adaptability in general) that the original design of a building plays a significant role in enabling adaptability in future alterations. Therefore, to address these gaps in CBA research, this paper's objectives are to (1) identify and analyse strategies that could enable CBA and (2) outline a conceptual design framework for the concept's practical application.…”
Section: Introductionmentioning
confidence: 77%
See 3 more Smart Citations